Penerapan Emotional Intelligence pada Pemimpin Usaha Mikro, Kecil, dan Menengah - Maulana, Ridwan; Agustina, Tri Siwi (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
This research explores the implementation of Emotional Intelligence among Micro, Small, and Medium Enterprises (MSMEs) leaders at Apotek Medical Plus. Through interviews and analysis, the study demonstrates that MSME leaders, such as the Finance Director as top manager and Pharmacist as first-level manager, have applied aspects of Emotional Intelligence, including self-awareness, self-regulation, motivation, empathy, and social skills. However, there remains room for improvement in this implementation. The research findings propose concrete steps for Apotek Medical Plus to enhance and maintain the application of Emotional Intelligence. These steps include fostering self-awareness through personal consultation sessions or anonymous surveys, cultivating self-regulation through mindfulness training, reinforcing motivation by providing career visions, deepening empathy through social activities, and enhancing social skills by attending seminars and receiving 360-degree feedback. These measures aim to ensure that the applied level of Emotional Intelligence can be sustained and even elevated for a better future.